Study the EGFR and HER2 Receptors Inhibitory Effect of Compounds in Siegesbeckia orientalis L. for Supporting Cancer Treatment - Thi Hang, Do; Hoang Mai, Tran; Thi Huong, Le; Thi Hong Khanh, Do; Thi Thuy, Nguyen; Van Khoi, Nguyen; Thi Thanh Binh, Nguyen; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 2, 2022)
Epidermal growth factor receptor ( EGFR ) and Human epithelium receptor 2 (HER2) are important targets in cancer treatment such as lung cancer, breast cancer. Siegesbeckia orientalis L. is a medicinal plant that has the ability to inhibit the proliferation of cancer cells. In this study, we evaluated the ability to inhibit EGFR and HER2 receptors of compounds from the Siegesbeckia orientalis L. by molecular docking method. Based on the published phytochemicals of Siegesbeckia orientalis L., we have collected 50 isolated compounds. Molecular docking results showed that the ability to inhibit EGFR was higher than erlotinib with 34 compounds, higher than icotinib with 7 compounds, higher than almonertinib with 21 compounds, and higher than olmutinib with 3 compounds; 4 compounds with higher ability to inhibit HER2 than neratinib, and 4 compounds may inhibit both EGFR and HER2 receptors simultaneously. Analysis of Lipinski's rule of five and predicting pharmacokinetic - toxicological parameters, we obtained two compounds that have drug-like properties. Therefore, these two compounds have the potential to be drugs that inhibit EGFR and HER2 receptors for cancer treatment and need to be studied further. Keywords EGFR, HER2, Molecular docking, Siegesbeckia orientalis L.